"The future is in your hands": temporality and the neoliberal self in the Czech voucher privatization. (2nd January 2022) - Babička, Martin
ABSTRACT: The Czech voucher privatization was a method of giving out state property to the population, mobilizing the majority of citizens, but also giving incentives for the founding of investment funds, which commissioned unprecedented marketing campaigns to divert shares from individuals, somewhat overshadowing the first efforts of the state to make everyone an investor. Examining the "first wave" in 1992, this paper argues that the voucher privatization was an attempt at not just an economic, but also a moral transformation, bidding to turn postsocialist people into neoliberal subjects, while framing this change as a return to normality. It analyses various sources of public economics, advertising and mass journalism. The paper thus goes beyond the existing historiography to show that voucher privatization gained popular support because of its promise that people would become the active creators of their own future. It also exhibits the relevance of the memory of state socialism for the popular sense-making of the endeavour to privatize – both for its legitimation and scepticism towards it. The attempt to make people into neoliberal subjects by means of "democratic capitalism" ultimately reinstituted the hierarchy between economic elites and lay citizens, as the very idea of creating a citizen-investor remained only short-lived.